Assessing ecotoxicity of an innovative bio-based mulch film: a multi-environmental and multi-bioassay approach - Barbir, J.; Arato, E.; Chen, C-Y.; Granberg, M.; Gutow, L.; Krång, A-S.; Kröger, S. D.; Leal Filho, W.; Liwarska-Bizukojc, E.; Miksch, L.; Paetz, K.; Prodana, M.; et al. (Frontiers in Environmental Science, 2023)
Among the highly diverse range of biobased polymers, polylactic acid (PLA) received vast attention in recent years due to its versatility for different applications and being the first commercially used polymer produced from renewable sources. Production and application of bio-based, biodegradable plastics will have one of the most crucial roles in tackling worldwide plastic pollution. Methods: This study is based on integrative ecotoxicological assessment of an innovative PLA-based agricultural mulch film (BPE-AMF-PLA), developed under the H2020 EU project “BIO-PLASTICS EUROPE”, towards organisms from different environmental compartments (soil, fresh water and marine) and from different trophic levels. Such comprehensive evaluation has an overarching goal to promote environmentally safe and sustainable use of these PLA-based plastics for agricultural and other potential applications. Results: Low-to-no phytotoxicity was obtained in both single-species standardized bioassays, and in a multi-species microcosms experiment. Earthworm reproduction was negatively affected at the lowest test concentration of 0.1% w/w of PLA-based plastic particles. For freshwater Daphnia, reproduction was found a sensitive endpoint, upon exposure to the leachates of the PLA-based plastic. However, the reported toxicity seemed to be caused by the presence of 2-methylnaphthalene, which can be avoided in the production process. As for the marine organisms, algae growth was inhibited with a LOEC = 25 g L−1, whereas test with brine shrimp only revealed stimulation of lipase upon digestion of micro-sized PLA-based plastics. Marine lugworm ingested pristine and UV pre-treated micro-sized plastics, yet without impact either on biological activity, or on the health of the test individuals. Discussion: The approach used in the present work will contribute to product development, environmental safety and sustainable applications of the PLA-based mulch film BPE-AMF-PLA, in the scope of project BIO-PLASTICS EUROPE. Furthermore, the tools and results obtained in this work are a relevant contribution in the framework development for additional support in the certification of the bio-based polymers, being aligned with European zero waste and non-toxicity strategies, certification, and regulations.